Pengaruh Implementasi Model Pembelajaran Snowball Throwing Terhadap Aktivitas Dan Hasil Belajar Siswa MTs Darussalam Sampang - Titin Hartini (PEDAGO BIOLOGI, 2018)
Abstrak : Education is a very good process. But, the goal of learning outcomes becomes an unresolved problem right now, this is because of the less interesting learning model. The learning model of snowball throwing is a quite interesting learning especially it is for student's learning outcomes. The purpose of this research is to describe the method of Snowball Throwing learning implementation based on learning outcomes, learning activities, and responding of MTs Darussalam Student's  of  snowball throwing learning. This type of research is pre experimental using pre-test and post-test of one design group. The research was conducted at MTs Darussalam Bunten Barat Ketapang Sampang Madura in May-August 2017. Data completion technique was done by methodology, student questionnaire method and observation method. The result of the research showed that there is an effect of snowball throwing learning model on student’s learning outcomes in subjects of living creature that is pretest average = 58,8 <postest = 87,2. Student activity in each group showed a presentation of 66.7% -100. Student's respond was categorized as good with the percentage value of students who stating Likes (S) and Very Likes (SS) equal to 86,72%.